A Model of Resource Allocation for Intercepting the Missile of Mass Destruction Considering Detection Contest. Issue 2 (January 2021) - Qu, Li; Han, Chenjing; Li, Yingchun; Ma, Ye; Gao, Kaiye; Peng, Rui
Abstract: With the development of military technology, missiles have played an essential role in modern war. Particularly, missiles have become main carriers of the weapons of mass destruction to strike the objective in a long distance. Thus, it is essential for the defender to intercept the missiles launched by the attacker. However, the intelligence about the attacking missiles obtained by the defender is usually incomplete, which depends on the detection contest where the defender tries to detect the attacking missile and the attacker tries to disturb the detection. This raises a problem about how to balance a certain amount of resources onto the interception missiles and detection contest for the defender in order to minimize the damage caused by attacking missiles. Therefore, considering detection contest, a model of resource allocation for missile interception is proposed in this study. The results show that the defender can obtain the strategy with the lowest damage by adjusting the allocation of resources. This provides an analytical method to calculate the damage caused by missiles of mass destruction under the missile interception considering detection contest.